The University of Gezira Advisory System: Academic Advising of Excellent Students - Mirghani, Omer Ahmed; Mohamed, Mohamed Elsanousi (Gezira Journal of Health Sciences, 2015)
Excellent students are the promising scientists and leaders of their professions in the future and hence universities must assume full responsibility of supporting and encouraging those students during the undergraduate and postgraduate studies; a policy which can help producing competent graduates who can contribute significantly in the total development of the country. Traditionally excellent students are rewarded by prizes and financial incentives and enrollment in the academic staff as teaching assistants. Although the university rewards are useful in motivating students to achieve excellence, their benefits to the excellent students and the universities are rather limited; they are usually late and do not contribute in strengthening and enriching the curricula. Faculties and departments should have a clear plan of guiding and supporting excellent students; to help them contribute in the academic activities and choose their future careers appropriately. The academic advising system was introduced very early during establishment of the University of Gezira (1975) and has been included in the academic regulations, ever since it has been implemented, upgraded and evaluated several times. Experience showed that it is useful and effective in helping students achieve the University requirements of graduation; teachers and students are now familiar with it. However the system focuses on poor students and neglects excellent students. Following is a proposal of academic advising of excellent students. Examples are drawn from the curriculum of the Faculty of Medicine and the model could be adopted by other faculties.